REVIEW OF COMPLETE PASSPORT ACCELERATION SERVICES ON THE SAME DAY TO MAKE PRIMA SERVICES AT THE NON TPI SPECIAL CLASS I IMMIGRATION OFFICE, SOUTH JAKARTA - Aisyah Mila Riski (Polteknik Imigrasi, 2019)
With the issuance of a policy regarding passport acceleration services completed on the same day, passport applicants can choose to complete their passport application on the same day the applicant submits the application to be a breakthrough alternative in meeting community needs and realizing immigration into a Clean and Serving Bureaucratic Area. The latest policy that benefits the community is the passport acceleration service on the same day. The implementation of this policy at the Immigration Office Class I for Non-TPI South Jakarta plays a role in realizing excellent service and eliminating gratuities.